Economic Policy, Economic Performance, and Elections - Harrington, Joseph E. (American Economic Review, 1993)
This paper explores the role of reelection pressures in determining economic policy. By assuming that voters are uncertain as to the efficacy of different policies, a reelection process is derived which depends on both a politician's past policies and the level of economic activity during his time in office. It is shown that the less uncertain are voters as to which policy is best, the more likely is a politician to manipulate policy for reelection purposes. Manipulation entails implementing the policy that is more likely to be well received rather than the one that maximizes income.